2016
DOI: 10.1128/mbio.02070-15
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus Methicillin Resistance Factor FmtA Is a d -Amino Esterase That Acts on Teichoic Acids

Abstract: The methicillin resistance factor encoded by fmtA is a core member of the Staphylococcus aureus cell wall stimulon, but its function has remained elusive for the past two decades. First identified as a factor that affects methicillin resistance in S. aureus strains, FmtA was later shown to interact with teichoic acids and to localize to the cell division septum. We have made a breakthrough in understanding FmtA function. We show that FmtA hydrolyzes the ester bond between d-Ala and the backbone of teichoic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 93 publications
0
58
0
1
Order By: Relevance
“…Our findings suggested that PS, G and PG could provoke protein-dependent antibiotic resistance, as the enzymes lysostaphin resistance protein A (LyrA) and methicillin resistance-associated FemA/B and FmtA [103][104][105] were detected in PS, PG and/or G biofilms already at the 18 h time point, implying that biofilms on other materials may be more susceptible to certain antibiotics. In our study, chemotolerance tests were executed with different antibiotics covering a broad spectrum of mechanisms of action: vancomycin (glycopeptide: inhibits cell wall synthesis by forming complexes with peptidoglycan precursors [106]), penicillin G (B-lactam: inhibits cell wall synthesis via preventing peptidoglycan polymerization [107]), doxycycline (tetracycline: inhibits protein synthesis by binding to the 30S subunit of the bacterial ribosome [108]) and levofloxacin (fluoroquinolone: inhibits bacterial DNA gyrase and topoisomerase IV in Gram-negative and Gram-positive bacteria, respectively, and blocking DNA replication [109]).…”
Section: Older Biofilms Are Not Always More Tolerant Than Younger Biomentioning
confidence: 75%
“…Our findings suggested that PS, G and PG could provoke protein-dependent antibiotic resistance, as the enzymes lysostaphin resistance protein A (LyrA) and methicillin resistance-associated FemA/B and FmtA [103][104][105] were detected in PS, PG and/or G biofilms already at the 18 h time point, implying that biofilms on other materials may be more susceptible to certain antibiotics. In our study, chemotolerance tests were executed with different antibiotics covering a broad spectrum of mechanisms of action: vancomycin (glycopeptide: inhibits cell wall synthesis by forming complexes with peptidoglycan precursors [106]), penicillin G (B-lactam: inhibits cell wall synthesis via preventing peptidoglycan polymerization [107]), doxycycline (tetracycline: inhibits protein synthesis by binding to the 30S subunit of the bacterial ribosome [108]) and levofloxacin (fluoroquinolone: inhibits bacterial DNA gyrase and topoisomerase IV in Gram-negative and Gram-positive bacteria, respectively, and blocking DNA replication [109]).…”
Section: Older Biofilms Are Not Always More Tolerant Than Younger Biomentioning
confidence: 75%
“…Kiriukhin and others have demonstrated that high NaCl concentrations inhibit transacylation from D-alanyl-DltC to the C2-OH of GroP and stimulate hydrolytic cleavage of the D-alanyl thioester (23,71). Alternatively, a recently described TA D-Ala esterase FmtA could play a role in reducing the LTA D-alanylation content under certain conditions (72). The mechanism of dealanylation by KOH treatment is more straightforward, as D-Ala LTA ester linkages are extremely labile to base.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome data (Mäder et al, ) suggested that gene 957 is in an operon with lcpB (Figure b), which is one of three wall teichoic acid (WTA) ligases present in S. aureus (Chan, Frankel, Dengler, Schneewind, & Missiakas, ; Over et al, ; Schaefer, Matano, Qiao, Kahne, & Walker, ). fmtA is located upstream of 957 and has been proposed to code for an esterase that can remove D‐alanine modifications from teichoic acids (Rahman et al, ) and is involved in methicillin resistance (Berger‐Bächi, Barberis‐Maino, Strässle, & Kayser, ). Genes coding for a predicted acetyltransferase and atl coding for the major S. aureus autolysin are found immediately downstream of the 957 operon (Oshida et al, ).…”
Section: Resultsmentioning
confidence: 99%